Encapsulation of Homogeneous Catalysts in Mesoporous Materials Using Diffusion‐Limited Atomic Layer Deposition. (27th December 2017) - Zhang, Shufang; Zhang, Bin; Liang, Haojie; Liu, Yequn; Qiao, Yan; Qin, Yong
Abstract: The heterogenization of homogeneous metal complex catalysts has attracted great attention. The encapsulation of metal complexes into nanochannels of mesoporous materials is achieved by coating metal oxides at/near the pore entrance by diffusion‐limited atomic layer deposition (ALD) to produce a hollow plug. The pore size of the hollow plug is precisely controlled on the sub‐nanometer scale by the number of ALD cycles to fit various metal complexes with different molecular sizes. Typically, Co or Ti complexes are successfully encapsulated into the nanochannels of SBA‐15, SBA‐16, and MCM‐41. The encapsulated Co and Ti catalysts show excellent catalytic activity and reusability in the hydrolytic kinetic resolution of epoxides and asymmetric cyanosilylation of carbonyl compounds, respectively. This ALD‐assisted encapsulation method can be extended to the encapsulation of other homogeneous catalysts into different mesoporous materials for various heterogeneous reactions.